Real-world multicenter experience with the CLEANER Vac™ thrombectomy system: An analysis of the first 30 patients - Peter Stibbs; Giles Martin; David Worth (Vascular Investigation and Therapy)
BACKGROUND: Venous thromboembolism, encompassing deep vein thrombosis (DVT) and pulmonary embolism, remains a significant clinical challenge with substantial morbidity and mortality. Traditional therapeutic approaches, including anticoagulation and systemic thrombolysis, often provide suboptimal outcomes in cases of large-volume thrombus burden, chronic thrombosis, or high-risk patient. Mechanical thrombectomy has emerged as an alternative, offering rapid thrombus removal while reducing the risk of major bleeding complications associated with systemic thrombolysis. The CLEANER Vac™ Thrombectomy System, developed by Argon Medical Devices, represents a novel advancement in percutaneous mechanical thrombectomy, designed to facilitate controlled, large-bore aspiration of venous thrombus in the peripheral venous system. OBJECTIVE: This study provides an in-depth real-world, multicenter evaluation of the first 30 patients treated with the CLEANER Vac system across multiple institutions. The primary objective was to assess the procedural efficacy of the device in thrombus clearance, while secondary objectives included evaluating patient demographics, procedural variables, success rates, and safety outcomes. METHODS: A retrospective, multicenter analysis was conducted across multiple institutions, evaluating patients with acute or subacute symptomatic venous thrombosis who underwent treatment with the CLEANER Vac thrombectomy device. Inclusion criteria included adults aged 18 years or older presenting with venous thrombus confirmed via duplex ultrasonography, computed tomography venography, or conventional venography. Patients were treated using a standardized protocol, with vascular access achieved via femoral, popliteal, or jugular veins depending on the thrombus location. The CLEANER Vac device was advanced to the thrombus site under fluoroscopic guidance, and aspiration thrombectomy was performed. Completion venography was utilized to assess clot clearance and adjunctive therapies such as angioplasty or catheter-directed thrombolysis were administered at the physician’s discretion when residual thrombus remained. Data collection included demographic details, pre- and postprocedure clot burden, thrombus clearance rates, adjunctive therapy use, and procedural complications. RESULTS: The study cohort comprised 30 patients with a mean age of 58.8 years (range: 28–88 years). The gender distribution was 50.0% male (n = 15), and 50.0% female (n = 15%). On average, 2.4 venous segments were treated per patient. The mean pretreatment clot burden was 95.4%, which was reduced to an average posttreatment clot burden of 6.0%, resulting in an average clot clearance rate of 93.1%. A total of 24 patients (82.8%) achieved ≥ 90% clot clearance, demonstrating a high procedural success rate. In the subset of patients requiring adjunctive therapy, rotational maceration was the most commonly used adjunct to aspiration thrombectomy. Balloon angioplasty was the most commonly utilized technique to optimize venous patency postthrombectomy. Procedural safety was favorable, with no major complications, including symptomatic PE, vessel perforation, or severe bleeding requiring transfusion. No minor complications such as access-site hematomas were observed in this first thirty patient cohort. CONCLUSIONS: This real-world, multicenter study highlights the efficacy and safety of the CLEANER Vac Thrombectomy System in the treatment of symptomatic venous thrombosis. The system demonstrated high rates of successful thrombus clearance with minimal procedural complications, supporting its role as an effective mechanical thrombectomy option for the management of peripheral venous thrombosis. The ability to achieve substantial clot burden reduction with a controlled aspiration mechanism provides an advantage over existing mechanical thrombectomy platforms. While these initial findings are promising, further prospective studies with larger patient cohorts and long-term follow-up are warranted to validate the sustained efficacy and durability of treatment outcomes.